선망과 폭력—허먼 멜빌의 『빌리 버드』 - 김미현 (미국학 논집, 2020)
Melville explores envy’s destructiveness in Billy Budd. Melville shows civilization and intellectuality can drive envy into the worst case of violence and moral violation. Claggart’s envy of Billy Budd is driven by his keen insight into Billy’s innocence and its “moral phenomenon.” Claggart’s false accusation of Billy of inciting the crew to mutiny can be a case of meaningless violence as he intends to destroy the goodness because he cannot have it. Vere adopts the sovereign role to determine “the state of exception” and makes Billy a victim of the political violence with his argument of “military necessity” in convicting Billy of murder of Claggart, a superior, and sentencing him to death. Agamben writes, the sovereign decision “suspends law in the state of exception and opens a sphere permitted to kill without committing homicide” and without religious meaning. Captain Vere joins Claggart in hidden envy of a model. For Vere, Nelson becomes a model of leadership, and Vere makes Billy “a surrogate victim” in Girard’s sense. Girard sees that violence from mimetic rivalry “always finds a surrogate victim” “if the initial object remains persistently out of reach and continues to provoke hostility.” In this sense, Vere’s violence toward Billy can be seen as a case of substitution in mimetic rivalry and scapegoating.
Keywords: Envy; Violence; Sacrifice; Herman Melville; Billy Budd